Does the renal expression of Toll-like receptors play a role in patients with IgA nephropathy? - Ciferska, Hana; Honsova, Eva; Lodererova, Alena; Hruskova, Zdenka; Neprasova, Michaela; Vachek, Jan; Suchanek, Miloslav; Zima, Tomas; Coppo, Rosanna; Tesar, Vladimir; Novak, Jan; Maixnerova, Dita (Journal of nephrology, 2020)
The onset of IgA nephropathy (IgAN), characterized by glomerular deposition of IgA-containing immune complexes, is often associated with synpharyngitic hematuria. Innate immune responses mediated by Toll-like receptors (TLR) may play a role in IgAN onset and/or progression. Here, we assessed the expression of TLR 4, 7, 8, and 9 in renal-biopsy specimens from patients with IgAN, with different degree of proteinuria and eGFR, compared with normal-kidney and disease-control tissues (ANCA-associated vasculitis). Renal-biopsy specimens from 34 patients with IgAN and 7 patients with ANCA-associated vasculitis were used. In addition, we used 15 healthy portions of renal-tissue specimens from kidneys after nephrectomy for cancer as control specimens. Expression of TLR 4, 7, 8, and 9 was assessed using immunohistochemical staining of paraffin-embedded renal-biopsy tissue specimens with specific antibodies and evaluated semiquantitatively by light microscopy. Linear discriminant analysis (LDA) was used to test whether intrarenal staining of TLR 4, 7, 8, and 9 distinguished patients with IgAN from controls or correlated with eGFR and/or proteinuria. eGFR was calculated using the creatinine-based formula. Moreover, the biopsies from patients with IgAN were scored according to the Oxford Classification. LDA showed that staining for TLR 4, 7, 8, and 9 was more intense in specimens from IgAN patients compared to normal kidney tissues. The intensity of intrarenal staining of TLRs discriminated four groups of IgAN patients with different eGFR and proteinuria and MEST scoring.
Keywords: ANCA-associated vasculitis; Toll-Like Receptors; stupeň závažnosti nemoci; hodnoty glomerulární filtrace; Case-Control Studies; lidé; IgA nephropathy; Renal insufficiency; toll-like receptory; studie případů a kontrol; Toll-like receptors; Glomerular Filtration Rate; IgA nefropatie; Humans; Renal biopsy; Glomerulonephritis, IGA; Severity of Illness Index